Growth and Flavonoid Content of Gynura procumbens (Lour) Merr. in Different Soil Water Content - Savitri, Evika Sandi; Khusnia, Farrikhatun (Jurnal Biodjati, 2019)
Gynura procumbens contains tannins, saponins, steroids, triterpenoids, essential oils and flavonoids which have bioactivity as a medicine for various diseases. One effort to obtain the quality of medicinal plants uses management of soil water content. The opti-mum of soil water content will support optimal growth of a plant. Whereas in conditions of low soil water content resulted in the induc-tion of the production of secondary metabolites as a self-defense sys-tem. This study aimed to determine the effect of soil moisture content on the growth and total content of plant flavonoids G. procumbens. This study was carried out experimentally using a one-factor com-plete randomized design (CRD) consisting of 4 treatments with five replications. The treatment used is the difference in soil water content of 40%, 60%, 80% and 100% field capacity. The data obtained in the form of quantitative data will be analyzed by One Way ANOVA Test. Measurement of the content of total flavonoid compounds was car-ried out using UV-Vis spectrophotometer analysis. The results of the study indicate the influence of soil moisture level on the growth and total content of G. procumbens. Parameter growth of fresh weight, dry weight, and root G. procumbens showed an increase in 40% soil water content. The flavonoid content showed the highest total flavo-noid content 18.884 mg/g in the 40% field capacity soil water contentÂ